2012
DOI: 10.1007/s00405-011-1912-4
|View full text |Cite
|
Sign up to set email alerts
|

Short tone bursts are better than clicks for cervical vestibular-evoked myogenic potentials in clinical practice

Abstract: Our aim is to compare short tone burst (STB)--and clicks--stimuli to evoke vestibular-evoked myogenic potentials (VEMPs) in healthy controls. A cross-sectional study in which VEMPs were measured in two sets of 185 and 55 normal volunteers by an air-conducted 500 Hz STBs and clicks, respectively. The test-retest reliability between different sessions was assessed in two subsets of 35 individuals. Moreover, 53 individuals were examined with both stimuli within the same session. Intraclass correlation coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…This stimulus has provided good reliability in eliciting VEMPs. 31,32 CVEMPs were recorded from an electrode montage consisting of a non-inverting electrode placed at the midpoint of the ipsilateral sternocleidomastoid muscle belly, an inverting electrode placed on the sternoclavicular junction, and a ground electrode placed on the manubrium sterni. The responses to 100 stimuli were averaged.…”
Section: Methodsmentioning
confidence: 99%
“…This stimulus has provided good reliability in eliciting VEMPs. 31,32 CVEMPs were recorded from an electrode montage consisting of a non-inverting electrode placed at the midpoint of the ipsilateral sternocleidomastoid muscle belly, an inverting electrode placed on the sternoclavicular junction, and a ground electrode placed on the manubrium sterni. The responses to 100 stimuli were averaged.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we attempted to record VEMPs from children by helping them to raise their heads during the recording. Furthermore, we used a 95-dB nHL tone burst instead of 90-dB nHL clicks, which were used in the study by Kelsch et al [2006], as a stimulus for eliciting VEMPs, since it has been shown that tone bursts are superior to clicks in eliciting VEMP responses [Murofushi et al, 1999;Viciana and Lopez-Escamez, 2012]. Of the children tested in this study, with an age range of 2-8 years, 70% were able to generate sufficient neck muscle activity (>150 μV) to successfully complete VEMP testing.…”
Section: Discussionmentioning
confidence: 99%
“…These authors recommended the use of short tone bursts, since a large inter-laboratory variability concerning click-evoked cVEMP latency and amplitude was evident. Most recently, Viciana and Lopez-Escamez (2012) indicated that 500-Hz short tone bursts elicited consistently larger amplitudes. The meta-analysis in the current study concurred with these findings, where CVs had a weighted mean of 92.94 mV (11.18) and TBVs a larger weighted mean of 122.16 mV (13.82).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the majority of data indicate short tone bursts to be superior to click stimuli when attempting to evoke cVEMP responses, since they produce larger cVEMP amplitudes, have better reliability across recording sessions, and have smaller inter-laboratory variability (Welgampola & Colebatch, 2001a;Murofushi et al, 1999;Basta et al, 2005;Wu et al, 2007;Viciana & Lopez-Escamez, 2012).…”
Section: Vestibular Function Testing Commonly Consists Of a Battery Omentioning
confidence: 99%